2011
DOI: 10.1111/j.1365-294x.2011.05386.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive conflicts in polyandrous and polygynous ant Formica sanguinea

Abstract: The occurrence of multiple reproductives within an ant colony changes the balance between indirect fitness benefits and reproductive competition. We test whether the number of matings by an ant queen (polyandry) correlates negatively with the number of reproductive queens in the colony (polygyny), whether the patrilines and matrilines differ in their contribution to the sexual and worker progeny and whether there is an overall reproductive skew. For these aims, we genotyped both worker and sexual offspring fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Task is largely determined by caste in some ants and several studies have found patriline variation in caste propensity in age-matched leaf-cutting ants, in which sperm use is essentially random (Hughes et al 2003;Boomsma 2007, 2008; Evison and Hughes 2011;Holman et al 2011). Similar genetic effects on caste also appear to occur in army ants, harvester ants and Formica ants (Rheindt et al 2005;Jaffé et al 2007;Smith et al 2008;Haapaniemi and Pamilo 2012). Recently, patriline variation in the propensity of workers of similar size and age to engage in foraging or waste management has also been found in leafcutting ants .…”
Section: Introductionmentioning
confidence: 78%
“…Task is largely determined by caste in some ants and several studies have found patriline variation in caste propensity in age-matched leaf-cutting ants, in which sperm use is essentially random (Hughes et al 2003;Boomsma 2007, 2008; Evison and Hughes 2011;Holman et al 2011). Similar genetic effects on caste also appear to occur in army ants, harvester ants and Formica ants (Rheindt et al 2005;Jaffé et al 2007;Smith et al 2008;Haapaniemi and Pamilo 2012). Recently, patriline variation in the propensity of workers of similar size and age to engage in foraging or waste management has also been found in leafcutting ants .…”
Section: Introductionmentioning
confidence: 78%
“…As a consequence, Formica ants are a model in studies of social organisation (e.g. [16], [20]), chemical recognition (e.g. [21][24]), social parasitism (exploitation of colony resources, [25]) and their role in forest ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence there is a wealth of molecular data available from social insect species on the number of males represented among a given queen's offspring, and the distributions of paternity among those males. Interestingly, the number of potential sires represented in a brood or in a queen's sperm storage organ has often been reported to be greater than the effective paternity (Fernández‐Escudero et al 2002; Boomsma et al 2009; Haapaniemi and Pamilo 2012). Moreover, many studies have revealed a mismatch between observed queen mating frequencies and actual numbers of sires (Boomsma and Ratnieks 1996; Baer 2011).…”
mentioning
confidence: 99%
“…Moreover, many studies have revealed a mismatch between observed queen mating frequencies and actual numbers of sires (Boomsma and Ratnieks 1996; Baer 2011). These discrepancies could arise from (1) stochastic events, such as insemination failure or male infertility (Garcia‐Gonzalez 2004); (2) factors leading to inequalities between fertilization success and paternity success, which include embryo or juvenile mortality resulting from intrinsic sire effects or genetic incompatibilities between a queen and potential sires (García–González 2008); or (3) as is common in other animal taxa, an outcome of sperm competition, cryptic female choice, or conflicting interests over paternity (Sundström and Boomsma 2000; Haapaniemi and Pamilo 2012). Currently however, no attempt has been made to assess variation in paternity skew across all the major social Hymenoptera clades where polyandry has evolved independently (Boomsma and Sundström 1998; Schlüns et al 2005), or to explicitly relate paternity skew to the number of potential sires.…”
mentioning
confidence: 99%